Pengaruh Brand Ambassador dan Social Media Marketing Melalui Instagram Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variabel Intervening (Studi Kasus Pada Pengguna Produk Wardah di Kota Padang) - Alifia, Annisa; Rahmidani, Rose (Jurnal Ecogen, 2025)
The research aims to analyze the influence  of Brand Ambassador and Social Media Marketing via Instagram on Purchase Decision, with Brand Image as an intervening variable.  The population in this study is all people in Padang city who have ever bought Wardah products, the number of which is not yet known. The determination of the number of samples in this study was 160 people using purposive sampling technique. The questionnaire was measured using a Likert scale calculation. The data analysis technique was descriptive, data verification, then SEM analysis with two stages in the form of testing the measurement model used for validity and reliability tests and testing the structural model used for causative tests. The results of the study show  Ambassador has a significant effect on Brand Image (β = 0.590, p < 0.001) and Purchase Decision (β = 0.290, p = 0.031). Similarly, Social Media Marketing significantly influences Brand Image (β = 0.410, p < 0.001) and Purchase Decision (β = 0.369, p = 0.006). Furthermore, Brand Image serves as an intervening variable, as evidenced by the indirect effect of Brand Ambassador (β = 0.178, p = 0.021) and Social Media Marketing (β = 0.124, p = 0.016) on Purchase Decision. These findings confirm that effective utilization of brand ambassadors and social media marketing strategies can strengthen brand image, ultimately enhancing purchase decisions. Therefore, marketers should optimize these strategies to increase product appeal among consumers.